Der deutsche Telekommunikationsmarkt im europäischen und internationalen Vergleich - Andreas Westermeier (Wirtschaftsdienst, 2014)
Die Bundesregierung hat vor Kurzem eine "Digitale Agenda" vorgelegt. Intelligente Hard- und Software und die Verknüpfung immer größerer Datensätze bieten erhebliche ökonomische Potenziale und bilden die Basis für Innovationen. Allerdings müssen hierfür auch die technischen Voraussetzungen gegeben sein. Der Autor sieht Deutschland im internationalen Vergleich gut aufgestellt, mahnt aber weitere Investitionen an. – – According to current discussions, the German and European market for telecommunications is not as competitive as in the US or Asia. This paper shows - based on official data - that Germany has a high availability of broadband internet connections. It is not the availability but the usage that lags behind. Fixed telephone calls as well as broadband internet connections are rather cheap in Germany, but to be prepared for the digitalisation of the economy and society, more investments in infrastructure are needed. Surprisingly the US does have a higher number of network providers than Europe. What is missing in Europe is a provider that covers all countries of the European Union; current EBITDA does not show that the European market is too fragmented to make a profi t.
Keywords: L52; L96; L98; 330; Telekommunikationsmarkt; Breitbandkommunikation; Infrastrukturinvestition; Internationaler Wettbewerb; Deutschland